2022
DOI: 10.1186/s12866-022-02642-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of probiotic and technological properties of Bacillus spp. isolated from Burkinabe Soumbala

Abstract: Background Soumbala is a highly loved alkaline traditional fermented food condiment in Burkina Faso. It harbors various microbiota dominated by fermentative Bacillus spp. as functional microorganism with little confirmed health-promoting properties. Methods The present study aimed to evaluate six Bacillus strains previously isolated and identified from soumbala. These strains were selected as presumptively safe bacteria for probiotic and technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The present study isolated and characterized local probiotics from different vegetables and fruits. Various researchers have reported the isolation of probiotics from different ecological environments ( Dabiré et al, 2022 , Roza et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study isolated and characterized local probiotics from different vegetables and fruits. Various researchers have reported the isolation of probiotics from different ecological environments ( Dabiré et al, 2022 , Roza et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endospore staining was used to determine the spore formation of bacteria. Gram’s and endospore staining was done by the protocol of ( Benson, 2002 , Dabiré et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Dabiré et al [48] conducted a study to investigate the probiotic attributes of presumed-safe Bacillus spp. strains isolated from soumbala, a traditional fermented food from Burkina Faso.…”
Section: Research On Bacillus Cabrialesii Around the Worldmentioning
confidence: 99%
“…Recent studies have identified bacteria from bee bread as potential probiotics [ 28 , 36 , 37 , 38 ]. Furthermore, certain strains of Bacillus and Lactobacillus isolated from fermented foods have shown promising probiotic potential [ 39 ]. Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%